2021
DOI: 10.1002/2688-8319.12089
|View full text |Cite
|
Sign up to set email alerts
|

Evidence shortfalls in the recommendations and guidance underpinning ecological mitigation for infrastructure developments

Abstract: 1. In the United Kingdom and European Union, legal protection of species from the impacts of infrastructure development depends upon a number of ecological mitigation and compensation (EMC) measures to moderate the conflict between development and conservation. However, the scientific evidence supporting their effectiveness has not yet been comprehensively assessed.2. This study compiled the measures used in practice, identified and explored the guidance that informed them and, using the Conservation Evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Existing evidence not applicable to area or region or issue; existing evidence narrow and systematic reviews lacking, inhibiting generalizability Cvitanovic et al, 2016;Christie et al, 2020;Gutzat & Dormann, 2020;Hunter et al, 2021 Complexity and uncertainty…”
Section: Appropriateness Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence not applicable to area or region or issue; existing evidence narrow and systematic reviews lacking, inhibiting generalizability Cvitanovic et al, 2016;Christie et al, 2020;Gutzat & Dormann, 2020;Hunter et al, 2021 Complexity and uncertainty…”
Section: Appropriateness Of Evidencementioning
confidence: 99%
“…Remarkably, few studies address this aspect of the science–practice interface (Fabian et al., 2019). Most of these rely only on interviews (Gutzat & Dormann, 2020) or surveys of conservation planners or practitioners (e.g., Cook et al., 2010; Fabian et al., 2019; Pullin & Knight, 2005); evaluate only the use of scientific evidence in the peer‐reviewed literature (Cvitanovic et al., 2016; Hunter et al., 2021); and focus on information used without further investigating the processes by which evidence is applied. We found only 1 study incorporating both formal document analysis and survey methods (Pullin et al., 2004); it examined management plans of major United Kingdom conservation organizations.…”
Section: Introductionmentioning
confidence: 99%
“…This is justifiable on the grounds of zu Ermgassen et al ( 2021) who identified in their sample of developments achieving net gain that the vast majority (93%) of biodiversity units were delivered on-site; although we recognise the government's own market analysis suggests up to 50% of units may be delivered off-site (eftec, 2021). In Section 5 we then draw on results from recent evaluations of Biodiversity Net Gain and species mitigation measures to discuss improvements required to deliver this aim (Hunter et al, 2021;zu Ermgassen et al, 2021).…”
Section: Potential Baseline Biodiversity Impacts Of Housing Expansion...mentioning
confidence: 99%
“…ensuring that regulators have sufficient tools to enforce the delivery of Biodiversity Net Gain; zu . In addition, the evidence base behind the effectiveness of species mitigation measures for housing development impacts remains weak, with only 29% of species mitigation measures demonstrably successful at preventing harms to wildlife of new housing (Hunter et al, 2021). Using only evidence-based mitigation techniques would increase confidence that housing expansion does not trade-off against wildlife abundance goals.…”
Section: Principles For Newbuildsmentioning
confidence: 99%
“…We examined the inclusion of evidence in conservation guidance in the United Kingdom and Ireland to understand the level of transparency in the following: methods of production, source of information underlying the recommendations, date of the source material used to write the guidance, and the reporting of uncertainty in the recommendations based on the strength of the evidence. Although well‐formulated and presented guidance can result in the effective translation of evidence into practice (Walsh et al, 2015), poorly formulated guidance can lead to misdirection or misguided decisions, resource waste and could even do more harm than good (Hunter et al, 2021; Pullin & Knight, 2005).…”
Section: Introductionmentioning
confidence: 99%